(untitled) (Journal of the College of Basic Education, 2025)
This research investigates the role of practical activities in improving science education quality and their impact on students’ academic performance in Iraq. It focuses on transitioning from theoretical learning to interactive, practice-based education that relies on experimentation. Practical activities are shown to be effective in fostering students’ critical and creative thinking skills, enabling them to better understand scientific concepts and connect them to real-world applications. The study highlights the challenges faced by Iraq’s educational system, such as limited resources, inadequate school infrastructure, and a lack of focus on practical activities in the curriculum. To address these issues, the research employed a dual methodology: descriptive-analytical to evaluate the current state of practical activities in Iraqi schools and experimental to assess their impact on student performance. The findings revealed that students engaged in practical activities (the experimental group) significantly outperformed their peers in the control group, who were taught using traditional methods. The experimental group’s average scores increased by 23% after implementing practical activities, underscoring their importance in the educational process. Observations, surveys, and interviews further demonstrated that practical activities enhance critical thinking skills, promote teamwork, and boost students’ motivation to learn.